2020
DOI: 10.1371/journal.pone.0236294
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering considerations for the heterologous expression of xylose-catabolic pathways in Saccharomyces cerevisiae

Abstract: Xylose, the second most abundant sugar in lignocellulosic biomass hydrolysates, can be fermented by Saccharomyces cerevisiae expressing one of two heterologous xylose pathways: a xylose oxidoreductase pathway and a xylose isomerase pathway. Depending on the type of the pathway, its optimization strategies and the fermentation efficiencies vary significantly. In the present study, we constructed two isogenic strains expressing either the oxidoreductase pathway (XYL123) or the isomerase pathway (XI-XYL3), and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…As previously reported, Δ pho13 improves the xylose fermentation capability of engineered strains of S. cerevisiae ( Ni et al, 2007 ; Van Vleet et al, 2008 ), and other studies have confirmed this with different strain backgrounds ( Fujitomi et al, 2012 ; Kim et al, 2013d ; Jeong et al, 2020 ). Although the detailed molecular mechanism remains unknown, Δ pho13 causes transcriptional activation of the genes involved in non-oxidative PPP ( Kim et al, 2015 ; Ye et al, 2019 ) and reduction of the dephosphorylation product of sedoheptulose-7-phosphate, suggesting the phosphatase activity of Pho13 ( Xu et al, 2016 ).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…As previously reported, Δ pho13 improves the xylose fermentation capability of engineered strains of S. cerevisiae ( Ni et al, 2007 ; Van Vleet et al, 2008 ), and other studies have confirmed this with different strain backgrounds ( Fujitomi et al, 2012 ; Kim et al, 2013d ; Jeong et al, 2020 ). Although the detailed molecular mechanism remains unknown, Δ pho13 causes transcriptional activation of the genes involved in non-oxidative PPP ( Kim et al, 2015 ; Ye et al, 2019 ) and reduction of the dephosphorylation product of sedoheptulose-7-phosphate, suggesting the phosphatase activity of Pho13 ( Xu et al, 2016 ).…”
Section: Resultssupporting
confidence: 83%
“…Saccharomyces cerevisiae plays an essential role in the production of lignocellulosic biofuels by fermenting lignocellulosic sugars, mainly glucose and xylose, which requires engineering of the yeast via a heterologous xylose pathway (Kim et al, 2013c;Richa et al, 2019). Current efforts on the metabolic engineering of yeast remain focused on improving the xylose fermentation yield and productivity under multiple stress conditions of lignocellulosic biomass hydrolyzates (Jeong et al, 2020;Qin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell quenching, intracellular metabolite extraction, and derivatization for intracellular metabolite analyses were performed as previously described [33,34]. Briefly, 5 mL of cell culture at the mid-exponential growth phase was quickly injected and quenched in 25 mL 60% (v/v) cold methanol with 10 mM HEPES (pH 7.1) at −40 • C. Quenched cells were centrifuged, and supernatants were discarded.…”
Section: Intracellular Metabolite Extraction and Derivatizationmentioning
confidence: 99%
“…The product of both pathways, xylulose is phosphorylated by xylulose kinase (XK) and then enters into the pentose phosphate pathway for conversion to ethanol. Comparison of both pathways in different S. cerevisiae strains using various substrates [ 13 16 ] revealed that the XI pathway always gave a higher ethanol yield than the XR/XDH pathway. When both pathways were introduced into a single S. cerevisiae strain, a synergistic effect on xylose fermentation was observed [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%